IN DEFENSE OF CURRICULUM PRACTICED THOUGHT IN DAILY SCHOOL - Rafael Marques Gonçalves; Leonardo Ferreira Peixoto (Universidade Estadual Paulista Júlio de Mesquita Filho, 2017)
This paper takes as its starting point the creation of a Common National Base Curriculum underway in Brazil, to discuss traditional and technologic bases of curriculum thought that support this policy, when analyzing three actions against the BNCC produced by representative entities of curriculum researchers. In this sense, focus our analysis on some of the actions produced by the Brazilian Association of Curriculum (ABDC) and the National Association of Graduate Studies and Research in Education (ANPEd): 1) the production of a dossier published in 2014 on the idea of National Base; 2) the campaign "You already have curriculum"; 3) the letter sent to the National Education Council (CNE) with an "explanatory memorandum against the Common National Base Curriculum". Understanding that the guarantee of cognitive justice is a precondition for ensuring social justice, it is the mister desinvizibilização those practiced curricula and thought in school everyday. We consider networks in knowledge production and the need to bring about practices and thoughts in a post-abyssal perspective.